1992
DOI: 10.1177/104225879201600303
|View full text |Cite
|
Sign up to set email alerts
|

Research at the Marketing Interface to Advance Entrepreneurship Theory

Abstract: The knowledge base for the emerging field of entrepreneurship should be interfunctional and interdisciplinary. Yet the functional discipline of marketing has contributed to the entrepreneurship field in only recent years. And entrepreneurship researchers and writers often address marketing superficially, without an awareness of sophisticated marketing concepts and methods. The objectives of this article are to identify key tangencies at the marketing/entrepreneurship interface, to provide relevant research so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(129 citation statements)
references
References 39 publications
5
122
0
2
Order By: Relevance
“…Almost a decade and a half later, after numerous researches of many authors, some of them who were optimistic (e.g., claimed that the relationship between entrepreneurship and marketing should still be examined, while others (e.g., Miles, Crispin, & Kasouf, 2011) pointed out that it is diffi cult to defi ne the entrepreneurship-marketing link. There exist signifi cant areas of overlap between the marketing discipline and the study of entrepreneurship, and managers should be prepared to "borrow boldly" from marketing in order to advance the theory of entrepreneurship (Hills & LaForge, 1992).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost a decade and a half later, after numerous researches of many authors, some of them who were optimistic (e.g., claimed that the relationship between entrepreneurship and marketing should still be examined, while others (e.g., Miles, Crispin, & Kasouf, 2011) pointed out that it is diffi cult to defi ne the entrepreneurship-marketing link. There exist signifi cant areas of overlap between the marketing discipline and the study of entrepreneurship, and managers should be prepared to "borrow boldly" from marketing in order to advance the theory of entrepreneurship (Hills & LaForge, 1992).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Marketing and entrepreneurship are broadening their fi eld of synergic activity, but some gaps in this interaction still remain (Bhuian, Menguc, & Bell, 2005). Numerous studies have indicated the link between marketing and entrepreneurship (Murray, 1981;Morris & Paul, 1987;Herron, Sapienza, & Smith-Cook, 1992;Hills & LaForge, 1992;Becherer & Maurer, 1998;Morris, Schindehutte & LaForge, 2002;Kraus, Harms, & Fink, 2010;Gilmore, 2011Kurgun, Bagiran, Ozeren, & Maral, 2011;Morrish, 2011;Busenitz, Plummer, Klotz, Shahzad, & Rhoads, 2014), but a number of research question have remained underexplored. This paper addresses the relative scarcity of scholarly work that directly tests the causality in the frequency domain between the entrepreneurial activities and marketing in the function of gaining and maintaining distinctive market advantage of a company.…”
Section: Introductionmentioning
confidence: 99%
“…The Marketing/ Entrepreneurship Interface Model (Hills and Laforge, 1992) emphasises the relationship between EO and MO. The manner in which companies choose to orient themselves when exposed to competition in international markets, greater complexity, dynamism and uncertainty is critical to their survival.…”
Section: The Relationship Between Market Orientation and Internationamentioning
confidence: 99%
“…For the purposes of cross-cultural generalization Hills and LaForge (1992) have emphasized the importance of conducting entrepreneurship research in international contexts. In line with this suggestion the questionnaire was mailed at three different European universities, namely University of Cambridge (United Kingdom), Eindhoven University of Technology (The Netherlands), and University of Ljubljana (Slovenia).…”
Section: Questionnaire Developmentmentioning
confidence: 99%